Estimation of tertiary dentin thickness on pulp capping treatment with digital image processing technology - Slamet Riyadi; Laila Ma’rifatul Azizah; Fauri Hakim; Cahya Damarjati; Sartika Puspita; Erma Sofiani (International Journal of Electrical and Computer Engineering (IJECE), 2020)
Dentists usually observe the tertiary dentin formation after pulp capping treatment by comparing periapical radiograph before and after treatment visually. However many dentists find difficulties to observe tertiary dentin and also they can’t measure exactly the thickness of the tertiary dentin. The aims of this study is to assist the dentists to measure the area of tertiary dentin and calculate the dentin formation using b-spline image processing. The dental radiograph of 38 patients of pulp capping in the Dental Hospital Universitas Muhammadiyah Yogyakarta, Indonesia. Each of patient visited dental hospital 3 times. First, the patient got an application of pulp capping material. Second, after one-week treatment and temporary restoration and the third, after more than one month with the composite as the final restoration. Every visited the patient take a radiograph. Dentist placed the dot from the patient's radiograph. The dots were combined and processed with digital image processing. The b-spline method changed the dot to one area. After the calculation, the dentist can see whether there was dentin formation which means it is one of the treatment success indicators. Dentist has the better view to measure the dentin formation by providing area value of its tertiary dentin thickness calculation. We compare the result to the program calculation using the b-spline method and visual observation from the dentist. This study indicated the thickness of tertiary dentin can be measured by this program with an accuracy of 94.2%. Therefore, dentist can make tertiary dentin thickness prediction from patient’s radiograph.